Gut Microbiota-Derived Metabolites and Their Role in the Pathogenesis of Necrotizing Enterocolitis in Preterm Infants: A Narrative Review - Livia Provitera; Andrea Tomaselli; Francesca Algieri; Matteo Tripodi; Genny Raffaeli; Ilaria Amodeo; Ludovica Raymo; Carolina Vittoria Bronzoni; Monica Fumagalli; Felipe Garrido; Giacomo Cavallaro (Metabolites)
Background: Necrotizing enterocolitis (NEC) is a severe gastrointestinal disease that occurs predominantly in premature infants and is characterized by the inflammation and necrosis of the intestine, showing high morbidity and mortality rates. Despite decades of research efforts, a specific treatment is currently lacking, and preventive strategies are the mainstays of care. This review aims to help understand the complex interplay between gut microbiota and their metabolites in NEC pathogenesis. In particular, we focused on how these factors can influence gut health, immune responses, and intestinal barrier integrity. Discussion: Current research has increasingly focused on the role of the gut microbiota and their metabolites in NEC pathogenesis, thanks to their involvement in modulating gut health, immune responses, and intestinal barrier integrity. Conclusions: A deeper understanding of the interplay between gut microbiota and their metabolites is essential for developing personalized strategies to prevent NEC. By targeting these microbial interactions, new therapeutic approaches may emerge that offer improved outcomes for preterm infants at a high risk of NEC.